Internal Communication Role in Improving Performance of Employees Hotel: Descriptive Study at Employees Sari Ater Hotel & Resort in Ciater, Subang Regency, West Java Province - Ruliana, Poppy; Andrini, Susi; Lestari, Puji; Indrianti, Yasinta; ., Sasmoko (International Journal of Engineering and Technology, 2018)
Communication problems are one of the most important for every organization because it is a tool that binds all management functions within the organization. The effectiveness of internal communication at Sari Ater Hotel & Resort is very central to the survival of an organization and the performance organizatonâ€™s of a hotel that can be seen from the communication hierarchy in vertical, diagional and horizontal communication. The concept of internal communication refers to the opinions of Ronald Adler and George Rodman, who argued that in the process of internal communication occurs through vertical communication process, horizontal communication and diagonal communication. The method used in this research is sirvey with descriptive research type with quantitative approach. This method is suitable because it only provides an overview of research related to the role of internal communication effectiveness in improving employee performance Sari Ater Hotel & Resort. The purpose of this study is to know and analyze the performance of employees of Sari Ater Hotel & Resort. The results show that the vertical and horizontal communication dimensions in internal organizational communication play a role and effective in improving employee performance Sari Ater Hotel & ResortÂ Â